NCOG-13. THE IMPACT OF CME ON THE KNOWLEDGE OF NEUROFIBROMATOSIS TYPE 1-RELATED TUMORS - Worst, Michelle (Neuro Oncol, 2020)
BACKGROUND: Neurofibromatosis type 1 (NF1) is an autosomal dominant genetic condition characterized by a wide spectrum of clinical findings. Patients with NF1 develop benign and malignant tumors along the nerves of the skin, brain, and other body parts. Due to the unique presentation of each patient, clinicians are challenged to stay current with emerging data and how best to integrate new agents into multidisciplinary treatment paradigms. The objective of this study was to assess changes in neurologists’ and pediatricians’ knowledge and confidence through participation in education regarding NF1 treatment. METHODS: The educational activity consisted of a 30-minute online enduring, 1 faculty, chapterized summary of a live symposium. Educational effect was assessed with a repeated pairs pre-/post-assessment study with a 3-item, multiple choice, knowledge questionnaire and one confidence assessment question. For all questions, each participant served as his/her own control. Pre- and post-assessment scores were compared to determine relative changes in the proportion of correct responses. A chi-square test assessed statistical significance at the P < 0.05 level. The activity launched 23(rd) December 2019; data were collected until 2(nd) April 2020. RESULTS: Overall, statistically significant improvements were seen after education for neurologists (N=171, P < 0.05) and pediatricians (N=260, P < 0.01). The relative improvement in correct answers was 26% for neurologists and 48% for pediatricians (percent of total correct responses pre-/post-assessment were 27%/34% and 23%/34%, respectively). Following the activity, 16% of neurologists and 22% of pediatricians had a measurable increase in confidence regarding their understanding of multidisciplinary management of NF1. CONCLUSIONS: Participation in an online, 30-minute enduring CME intervention resulted in statistically significant improvements in knowledge and confidence of neurologists and pediatricians, that result in improvements in clinical care. Continued educational activities are paramount to address residual gaps and further increase clinicians’ confidence in this clinical setting.